Sistema de gestión de procesos administrativos de Subasta Inversa electrónica y Catalogo Electrónico de Contratación Pública aplicando tecnologías BPM, en el Gobierno Autónomo Descentralizado Provincial de Los Ríos. - Carriel Álvarez, Henrry David (2014)
This system was created by applying BPM technology Business Process Management and Business Process Management, which allows you to manage business processes and business and the benefit of the tasks are automated, monitored is obtained, and optimized to meet the objectives of the Gobierno Autonomo Desentralizado Provincial de Los Rios which are to promote the continuous improvement of technical and administrative procedures to ensure compliance with the Institutional Mission. With the help of a technological tool ProcessMaker can control workflows Procurement processes which are involved in electronic reverse auction and e- Books which are standardized processes, these workflows are the current requirements and needs GADPLR why such research is developing. For something a respective survey and interview personnel working in the facility to check the applicant need to research, and so once confirmed shortcomings in how the documentation is generated in each of the given tasks to complete was made a process , we proceeded to recommend the implementation of the system...